Konsentrasi Merkuri (Hg) pada Air Laut di Area Budidaya Teluk Manalu Kabupaten Kepulauan Sangihe - Bawelle, Eunike; Undap, Suzanne L.; Kusen, Diane J.; Pangemanan, Novie P. L.; Tumembouw, Sipriana S.; Wantasen, Adnan S.; Langi, Edwin O. (e-Journal BUDIDAYA PERAIRAN, 2020)
The aims of this research were to determine the concentration of mercury, and knowing the water quality in aquaculture area of Manalu Bay Sangihe Islands Regency. The method used in determine the research station is purposive sampling method or deliberate sampling with consideration that station 1 is near the gold mine, station 2 is the area aquaculture activities and station 3 is far from the gold mean and aquaculture activities. The data used in this research were sourced from primary data (sea water sampling used a sampling technique for Hg testing and direct measurement of water quality parameter) and secondary data (journals, books and other supporting documents that support research). The result detected the concentration of Hg content at station 1, 2 and 3 were <0,0003 mg/l below the sea water quality standards for marine biota (0,001). The parameter quality data of the water are temperature ranged between 31-32 0C, pH 6,8-7,1 and salinity 32-34 ppt. In general, the presence of chemical physics parameters in Manalu Bay was good condition and suitable for aquaculture after being compared with Kep. MENLH No. 51/2014, Attachment III concerning Sea Water Quality Standards for Marine Biota.